Insurance Value of International Reserves : An Option Pricing Approach - Lee, Jaewoo (Washington, D.C. : International Monetary Fund, 2004)
A quantitative framework is developed to bring forward the insurance motive of holding international reserves. The insurance value of reserves is quantified as the market price of an equivalent option that provides the same insurance coverage as the reserves. This quantitative framework is applied to calculating the cost of a regional insurance arrangement (e.g., an Asian Monetary Fund) and to analyzing one leg of an optimal reserve-holding decision.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet